PENGEMBANGAN MEDIA PEMBELAJARAN WOODEN TANGRAM PUZZLE BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN PEMAHAMAN KONSEP BANGUN DATAR SISWA KELAS IV SDN 4 NGAWEN - Hidayati, Maynurmala; Cahyadi, Fajar; Patonah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Understanding the concept of plane figures is an important basic competency in elementary school mathematics learning, but it is often difficult for students due to its abstract nature. This study aims to develop an Augmented Reality (AR)-based Wooden Tangram Puzzle learning media and test its feasibility, practicality, and effectiveness in improving the understanding of plane figures concepts for fourth-grade students. The study used the Research and Development (R&D) method with the ADDIE model. The subjects were 19 fourth-grade students of SDN 4 Ngawen. Data collection techniques included validation questionnaires from media experts and material experts, teacher and student response questionnaires, and pretest and posttest tests. Data were analyzed using quantitative descriptive analysis and t-test. The results showed that the media was declared very feasible by media experts (96%) and material experts (99%), very practical based on student responses (94.74%) and teachers (95%), and effective in improving the understanding of plane figures concepts with a t-test significance value of 0.016 <0.05. Thus, the AR-based Wooden Tangram Puzzle media is suitable for use as a mathematics learning medium in elementary schools.